ANALISIS STRATEGI PEMASARAN DALAM IKLAN AQUA ‘Tidak Semua Air Itu AQUA’ PADA ERA DIGITAL - Syabrina Octaviani; Yushie Maria Hutagalung; Dhea Annatasya; Rahel Anastasia (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
In the digital age, advertising marketing strategies have become crucial for bottled water products, including AQUA. This study aims to analyze the marketing strategy in the “Not All Water is AQUA” advertisement in the digital age using a qualitative approach to understand the message, communication techniques, and the effectiveness of digital strategies in building consumer trust. The results of the study indicate that the integration of conventional and digital strategies through informative messages and the effective use of digital platforms increases consumer reach and engagement. The novelty of this research lies in the presentation of a model for adapting classic messages into digital content that is relevant to the Fast-Moving Consumer Goods industry, providing an academic contribution in the form of strategic guidance for well-known brands in facing digital transformation. Overall, the flexibility of marketing strategies has been proven to strengthen brand awareness amid intense industry competition.